The Role of Investments in Developing A Green Economy in Our Country (International Journal of Scientific Trends, 2024)
This article is devoted to the importance of investments in the development of a green economy in our country. The work analyzes various instruments of "green" financing and the features of their use. The Uzbek and foreign experience of socially-oriented investment, as well as the trends and barriers to its development are considered. Conclusions are made about the effective configuration of the state and the private sector to stimulate "green" investments. The scientific significance of the study of this topic lies in the development of theoretical provisions related to investing in "green" projects with various financial instruments.